A Eurocentric Reflection in Josep Conrad’s Heart of Darkness - Aydın, Asım (Journal of History Culture and Art Research, 2018)
The two continents, African and European have been in conflict for centuries and their hostility and aggression are derived from two distinct perspectives and portrayals on both sides. The African continent, especially with the start of the exploration of Africa as a matter of colonial and imperial concerns and interests, became a place mostly identified with perceived negative aspects of the country from a European perspective, such as savagery, primitiveness, inferiority, political instability, and conflicts especially in Western literature (European literature). As it is described in Joseph Conrad’s Heart of Darkness by the narrator Marlow travelling along the Congo River, Africa is a ’dark place’ of the earth. On the contrary, European Continent, namely the Western World is depicted through predominant Eurocentric perception thanks to which Europe has been looked upon by many people as a privileged place in the world. Eurocentrism is a way of seeing the world from a European point of view situated at the high pillar constructed by the European ego. From this high pillar, the European superior ego looks down upon the others who are expected to suffer from a sense of inferiority.